Anxiety, depression, and attachment before and after the first‐trimester screening for Down syndrome: comparing couples who undergo ART with those who conceive spontaneously. (5th October 2015) - Udry‐Jørgensen, Laura; Darwiche, Joëlle; Germond, Marc; Wunder, Dorothea; Vial, Yvan
Abstract: Objectives: This study's aim was to describe the emotional status of parents to be before and after the first‐trimester combined prenatal screening test. Methods: One hundred three couples participated, of which 52 had undergone an in vitro fertilization/intracytoplasmic sperm injection treatment [assisted reproductive technology (ART)] and 51 had conceived spontaneously. Participants completed the state scale of the State‐trait Anxiety Inventory, the Edinburgh Depression Scale, and the Maternal and Paternal Antenatal Attachment Questionnaire before the first‐trimester combined prenatal screening test at around 12 weeks of gestational age (T1) and just after receiving the results at approximately 14 weeks of gestational age (T2). Results: We observed a significant decrease in anxiety and depression symptoms and a significant increase in attachment from T1 to T2. Results showed no differences between groups at either time point, which suggests that ART parents are more similar to than different from parents conceiving spontaneously. Furthermore, given the importance of anxiety during pregnancy, a subsample of women with clinical anxiety was identified. They had significantly higher rates of clinical depression and lower attachment. Conclusions: These results indicate that, regardless of whether conception was through ART or spontaneous, clinical anxiety in women over the prenatal testing period is associated with more vulnerability during pregnancy (i.e. clinical depression and less attachment to fetus). © 2015 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Prenatal testing is known to be emotionally distressing. What does this study add? This study adds to our knowledge about how the prenatal screening test at around 12 weeks of gestational age affects parents who conceive via assisted reproductive technology. The influence is similar whatever the mode of conception: Afterwards, anxiety and depression decrease, and prenatal attachment increases. Clinical anxiety in women during this period is associated with vulnerability to other risk factors, whatever the mode of conception.